(12y3 + 9 y2 + 21y)

Question

Asked 4/8/2012 7:59:05 PM

Updated 6/4/2014 8:21:17 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [6/4/2014 8:21:17 AM]

s

user1583|Points 1061|

user1583|Points 1061|

J_ME|Points 35|

Question

Asked 4/8/2012 7:59:05 PM

Updated 6/4/2014 8:21:17 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [6/4/2014 8:21:17 AM]

Rating

8

12y^3 + 9 y^2 + 21y = 3y(4y^2 + 3y + 7)

Added 6/4/2014 8:18:13 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/5/2014 4:12:40 AM]

8

(10x^2 – 14x – 12) ÷ (5x + 3)

= (5x + 3)(2x - 4)/(5x + 3)

= 2x - 4

= (5x + 3)(2x - 4)/(5x + 3)

= 2x - 4

Added 6/4/2014 8:21:09 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/5/2014 4:13:07 AM]

5x+2x^2+8x+34+8x+12x=

Question

Not Answered

Updated 7/16/2014 2:02:29 AM

1 Answer/Comment

5x+2x^2+8x+34+8x+12x=2x^2+33x+34

Added 7/16/2014 2:02:29 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:18:12 AM]

(5x^2 + 3x ) + ( 2x + 5) **Weegy:** First, get rid of the parentheses. 5x^2+3x+2x+5. Second, addition. 5x^2+5x+5 Third, divide everything by 5. x^2+x+5 **User:** (5x – 5 ) – ( 3x – 3) **Weegy:** please indicate what you would like to solve for or how you would like to solve this, you did not give enough information for me to do anything (More)

Question

Updated 9/18/2016 2:46:08 PM

2 Answers/Comments

(5x – 5 ) – ( 3x – 3) **Weegy:** is equal to 8x **User:** (8x – 2) + (7x + 6) **User:** (4x – 3.5) – (3x + 1.7) **Weegy:** First, get rid of the parenthese, 4x-3.5-3x-1.7 Second, Subtraction, x-5.2. x-5.2x is the answer. **User:** (12y3 + 9 y2 + 21y) ÷ 3y **Weegy:** x+3y=-15
3y=-x-15
y=(-1/3)x-5 (More)

Question

Updated 9/5/2014 4:11:57 AM

4 Answers/Comments

(5x – 5 ) – ( 3x – 3)

= (5x - 5) + (-3x + 3)

= 2x - 2

= (5x - 5) + (-3x + 3)

= 2x - 2

Added 9/5/2014 4:09:25 AM

This answer has been confirmed as correct and helpful.

(8x – 2) + (7x + 6) = 15x + 4

Added 9/5/2014 4:09:41 AM

This answer has been confirmed as correct and helpful.

(4x – 3.5) – (3x + 1.7)

= (4x - 3.5) + (-3x - 1.7)

= x - 5.2

= (4x - 3.5) + (-3x - 1.7)

= x - 5.2

Added 9/5/2014 4:10:06 AM

This answer has been confirmed as correct and helpful.

(12y^3 + 9y^2 + 21y) ÷ (3y)

= (12y^3/3y) + (9y^2/3y) + (21y/3y)

= 4y^2 + 3y + 7

= (12y^3/3y) + (9y^2/3y) + (21y/3y)

= 4y^2 + 3y + 7

Added 9/5/2014 4:11:57 AM

This answer has been confirmed as correct and helpful.

33,820,501

questions answered

There are no comments.